(untitled) (The Review of Diabetic Studies, 2025)
Background: The increasing digitization of healthcare has amplified cybersecurity threats, placing patient safety and data privacy at risk. Nurses, as frontline caregivers and primary users of electronic health records (EHRs), play a critical role in maintaining cybersecurity hygiene. However, the nursing profession remains underrepresented in formal cybersecurity protocols, training, and governance structures within healthcare systems. Aim: This systematic review aims to explore the role of nursing in cybersecurity management within digital healthcare environments, highlighting how nurses contribute to cyber defense, the challenges they face, and strategies to strengthen their capacity in this evolving domain. Method: A systematic review was conducted using five databases, such as PubMed, CINAHL, Scopus, ScienceDirect, and Google Scholar, targeting studies published between 2021 and 2025. Ten primary articles were selected based on predefined inclusion and exclusion criteria. PRISMA guidelines were followed, and quality appraisal was performed using a structured matrix. Results: Seven core themes emerged: nurse training and education, technological integration, institutional policy inconsistencies, human factor vulnerabilities, interdisciplinary collaboration, preparedness through simulations, and digital infrastructure security. While most studies emphasized the rising importance of nursing in cyber readiness, they also revealed a lack of standardized education and limited involvement of nurses in policy development. Nurses expressed willingness to engage more deeply in cybersecurity initiatives when adequately trained and supported. Conclusion: Nurses are critical to cybersecurity resilience in digital health. Strengthening their role through targeted education, policy inclusion, and interdisciplinary collaboration can significantly reduce cyber risks and enhance patient safety.